Pemanfaatan Jaringan Nirkabel Di Kampus Sekolah Tinggi Teknologi Adisutjipto Untuk Komunikasi Radio Dua Arah Pada Smartphone Berbasis Android - Wintolo, Hero; Susanto, Basuki Nugroho (SENATIK STT Adisutjipto, 2017)
The importance of communication increases development of information and communication technology in world so rapidly, especially in telecommunications equipment. Mobile phone or smart phone is one type of communication tools that provide communication services to a wide range of features offered but the services offered are not free. Handy Talky is applications and services to communicate for free with the use of smart phones based on Android and has a wifi enable this feature. This communication utilizing wifi network at a frequency of 2.4 GHz as to communication network. Test the application is done by trying on some of the features on a smart phone application with different specifications. From the test produced a smart phone that can run the application properly in some smart phones with Android operating system version 4.2 and above, and the smartphone is connected to a wifi network